Relevance of Civic Education With The Awareness in Building National Resourcesbas the Embodiment of the National Defense - Seri Wati Ginting; Miki Tjandra; Hendra Setiawan (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
Civic Education teaches the values of life that are manifested in daily behavior, such as accepting the diversity of the Indonesian nation. The existence of hate speech and blaming each other is a reflection of the failure of the nation. This research aims to develop Civic Education courses so that they can raise students' awareness to become good and educated citizens. Qualitative descriptive method examines and analyzes students' understanding of the relevance of Civic Education with national resources embodied in state resilience. The findings from this study show that some students are aware of the relationship between civic education and human resources but the role models of educators, education staffs, religious leaders, political leaders, and community leaders are still lacking.Pendidikan Kewarganegaraan mengajarkan nilai-nilai hidup yang terwujud dalamperilaku sehari-hari, seperti menerima keberagaman bangsa Indonesia. Masih adanyaujaran kebencian dan sikap saling menyalahkan menjadi cerminan kegagalan berbangsa.Penelitian bertujuan mengembangkan mata kuliah Pendidikan Kewarganegaran agarmampu menumbuhkan kesadaran mahasiswa untuk menjadi warga negara yang baik danterdidik. Metode deskriptif kualitatif mengkaji dan menganalisis pemahaman mahasiswatentang relevansi Pendidikan Kewarganegaraan dengan sumber daya nasional yangterwujud dalam ketahanan negara. Temuan dari penelitian memperlihatkan sebagianmahasiswa menyadari adanya keterkaitan antara pendidikan kewarganegaraan dengansumber daya manusia namun keteladanan dari tenaga pendidik, tenaga kependidikan,pemuka agama, tokoh politik, dan tokoh masyarakat masih kurang.